2022
DOI: 10.3390/ijerph19073871
|View full text |Cite
|
Sign up to set email alerts
|

Association between Healthy Lifestyle (Diet Quality, Physical Activity, Normal Body Weight) and Periodontal Diseases in Korean Adults

Abstract: This study aimed to investigate the association between healthy lifestyle (HLS; i.e., diet quality, physical activity, normal weight) and periodontal diseases in Korean adults. Studying this association may help inform future intervention programs aimed at preventing the development of periodontal diseases. Raw data of the Korea National Health and Nutrition Examination Survey (KNHANES) VII (2016–2018) were used. Data from 12,689 adults aged 19 years and over who had a periodontal examination were analyzed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…There is substantial evidence supporting a strong association between periodontitis and micronutrient intake [49][50][51][52][53][54][55]. Varied studies have been conducted in different directions to evaluate the association between periodontitis and micronutrient intake [45,[56][57][58][59][60]. Existing studies tend to explore the correlation using linear models, showing that associations between micronutrient intake and some other diseases were complex and nonlinear [61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence supporting a strong association between periodontitis and micronutrient intake [49][50][51][52][53][54][55]. Varied studies have been conducted in different directions to evaluate the association between periodontitis and micronutrient intake [45,[56][57][58][59][60]. Existing studies tend to explore the correlation using linear models, showing that associations between micronutrient intake and some other diseases were complex and nonlinear [61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, comparison with relevant findings from other published studies was not possible because previous studies on the association between PA and periodontitis did not perform sex-stratified analyses. 10,11,13 However, one potential explanation is that risk factors for periodontitis, such as smoking, were more prevalent among men than women.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are in agreement with those from previous studies. 10,11,13 Low levels of PA were associated with a higher prevalence of periodontitis in the Jordanian population 10 and among Korea National Health and Nutrition Examination Survey VII participants 13 and National Health and Nutrition Examination Survey (NHANES) III participants. 9 In one randomized controlled trial, a significant improvement in periodontal health was found after 6 months of exercise intervention in patients with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations